Improving Children's Independence Through the Project Based Learning Model Group A - Normila Normila; Muhammad Yusuf; Noor Baiti; Herman Taufik (EDUJAVARE: International Journal of Educational Research, 2025)
Early childhood is a critical period in which foundational aspects of personality and character are established. This research aims to enhance the independence of early childhood learners through the application of the Project Based Learning (PjBL) model in Group A at Raudhatul Athfal Harapan Ibu, Desa Labat Muara, Kecamatan Aluh-Aluh, Kabupaten Banjar. Independence is a crucial aspect of early childhood development, reflecting a child's ability to perform tasks without relying on others. The PjBL model was chosen because it provides meaningful, contextual, and active learning experiences through project activities that directly involve children. The research employed a Classroom Action Research (CAR) method conducted in two cycles. Each cycle consisted of planning, action, observation, and reflection. The subjects were 15 children in Group A, while data were collected through observation, documentation, and field notes. Project activities in Cycle I involved making pencil holders from used cardboard and straws, while Cycle II involved creating pencil holders decorated with flannel fabric. The results indicated a significant increase in children's independence after implementing the PjBL model, as evidenced by the shift in children’s independence categories and improvement in key indicators such as initiative, responsibility, and decision-making. Therefore, it can be concluded that the PjBL model is effective in enhancing independence in early childhood education settings.